Towards sustainable business models in the circular bioeconomy: The case of bio-based fertilizers - VIKTORIJA JANKULOSKA (Bio-based and Applied Economics)
Bio-based fertilizers (BBFs) offer a sustainable solution to the environmental and economic challenges of conventional fertilizers by enhancing nutrient recycling and soil health, aligning with EU strategies. Despite the availability of frameworks like the Business Model Canvas (BMC), these models have not been comprehensively applied in the context of BBFs. This paper addresses this gap by using the BMC framework to provide a holistic overview of BBF business models, integrating economic, environmental, and social dimensions. A literature review was conducted, covering studies on certain aspects of BBF business models; however, due to gaps, broader bioeconomy studies and research on various business model elements were included to draw relevant insights. The paper presents a comprehensive analysis of key aspects related to BBF commercialization, with sustainability as a core objective, offering valuable insights for stakeholders in the fertilizer and agricultural sectors, policymakers, and researchers to support strategies for a sustainable circular bioeconomy.